2004
DOI: 10.1038/sj.emboj.7600454
|View full text |Cite
|
Sign up to set email alerts
|

Small proline-rich protein 1A is a gp130 pathway- and stress-inducible cardioprotective protein

Abstract: The interleukin-6 cytokines, acting via gp130 receptor pathways, play a pivotal role in the reduction of cardiac injury induced by mechanical stress or ischemia and in promoting subsequent adaptive remodeling of the heart. We have now identified the small proline-rich repeat proteins (SPRR) 1A and 2A as downstream targets of gp130 signaling that are strongly induced in cardiomyocytes responding to biomechanical/ischemic stress. Upregulation of SPRR1A and 2A was markedly reduced in the gp130 cardiomyocyte-restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 58 publications
9
94
0
Order By: Relevance
“…In the biliary tract, the expression of SPRR2 members is highly induced under stress injury [29]. Similarly, SPRR1A and SPRR2A are strongly induced in cardiomyocytes responding to biomechanical/ischemic stress, and these proteins could protect cardiomyocytes against ischemic injury [30]. The SPRR2A protein was also reported to be highly induced in gastric mucosa upon Helicobacter pylori infection in the human stomach [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the biliary tract, the expression of SPRR2 members is highly induced under stress injury [29]. Similarly, SPRR1A and SPRR2A are strongly induced in cardiomyocytes responding to biomechanical/ischemic stress, and these proteins could protect cardiomyocytes against ischemic injury [30]. The SPRR2A protein was also reported to be highly induced in gastric mucosa upon Helicobacter pylori infection in the human stomach [31].…”
Section: Discussionmentioning
confidence: 99%
“…SW480/ SPRR3 cells showed a high anchorageindependent proliferation rate, supporting the hypothesis that increased SPRR3 plays a role in colorectal tumorigenesis. It has been reported that SPRR1A protein is upregulated in, and is protective against, hypoxia-induced stress (10). To further elucidate the mechanisms of molecular control of SPRR3 in colorectal cancer, we next examined the effect of SPRR3 on AKT signaling.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…SPRR proteins are known to be markers for terminal squamous cell differentiation, but they also function in nonsquamous tissues (9). For example, SPRR1A is induced by and is protective against ischemic stress in cardiomyocytes (10). It has recently been reported that SPRR3 is upregulated in celiac disease and also by prolonged exposure to cyclic strain (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Pradervand (50) Biomechanical/ischemic stress and remodeling (heart) SPRR1A, SPRR2A 2-35-fold induction 4 days after pressure over load or after one week in myocytes near infarcts; myocytes with transduced expression showed resistance to ischemic injury (mice) Gotter (51) Cultured (thymic epithelium) SPRR1B SPRR upregulated in cultured thymic epithelium; likely related to squamous differentiation (human) Bonilla (52) Nerve injury, axonal outgrowth, remodeling, repair (peripheral nerves) SPRR1A > 60-fold induction in injured peripheral neurons; associated with axonal outgrowth (mice) Fischer (53) Injury, growth, and remodeling in (central neurons)…”
Section: Sprr2amentioning
confidence: 99%